Do related party transactions affect insider trading? The moderating role of ESG - Almutairi, A.; Evans, Robert; Eulaiwi, Baban; Abdelazim, S.I.; Diab, A. (2025)
Purpose: This study aims to investigate the association between related party transactions (RPTs) and insider trading behaviour as well as the moderating role of environmental, social and governance (ESG) on the association between RPTs and the extent of corporate insider trading. Design/methodology/approach: This study used a sample of the top 300 companies listed on the Australian Securities Exchange from 2008 to 2019 and analysed data using OLS regression and generalised method of moments. Findings: This study found a significant and positive association between RPTs and insider trading dominated by buy trades. However, this study observed that ESG strength reduces the association between RPTs and insider trading dominated by buy trades. Research limitations/implications: The findings of this study highlight to regulators the value of considering disclosure on RPTs and insider trading to improve and refine regulations and promote compliance. Originality/value: This study contributes to the dearth literature on the association between RPTs and insider trading as well as the potential moderating factors affecting such a relationship.